2008
DOI: 10.1016/j.genhosppsych.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of body dysmorphic disorder in an adult inpatient setting

Abstract: Objective-Body dysmorphic disorder (BDD), a distressing or impairing preoccupation with an imagined or slight defect in appearance, is an often-severe, understudied disorder. We determined BDD's prevalence and clinical features on a general adult psychiatric inpatient unit. To our knowledge, only one previous prevalence study has been done in this setting. Method-One hundred patients completed 3 self-report measures: the Body Dysmorphic Disorder Questionnaire (BDD-Q), Beck Anxiety Inventory (BAI) and Center fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 34 publications
0
77
0
4
Order By: Relevance
“…In the American studies BDD prevalence was found to be 12.9-11%, in the German and the British studies the prevalence rates were 1.9% and 5.8%, respectively 8,[16][17][18] . Our findings are lower than the American studies whereas they are in accordance with the British study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the American studies BDD prevalence was found to be 12.9-11%, in the German and the British studies the prevalence rates were 1.9% and 5.8%, respectively 8,[16][17][18] . Our findings are lower than the American studies whereas they are in accordance with the British study.…”
Section: Discussionmentioning
confidence: 89%
“…In these 4 studies prevalence rates vary between 16% and 1.9%. This high range in prevalence might be both due to cultural differences and methodological differences 8,[16][17][18][19] . In our study we both aimed to evaluate the prevalence in Turkey and decrease the literatural ambiguity.…”
Section: Bulgularmentioning
confidence: 99%
“…For a second opinion a psychiatrist, who was experienced in diagnosing BDD, could be consulted via telephone. As the physical defect must be nonexistent or slight to meet the diagnostic criteria, the women's perceived appearance flaws were assessed by the interviewer using a Likert-scale, similar to rating scales used in previous research (Dufresne et al, 2001;Conroy et al, 2008;Conrado et al, 2010). The scale ranged from 1 to 3; 1 = no flaw present, 2 = minimal/slight flaw present, 3 = flaw present and clearly noticeable within conversational distance.…”
Section: Methodsmentioning
confidence: 99%
“…Using structured clinical interviews examining community samples, prevalence rates of 0.7-3% have been reported (Faravelli et al, 1997;Bienvenu et al, 2000;Otto et al, 2001). Studies of psychiatric samples have reported BDD in 2.6-16.0% of patients (Zimmerman and Mattia, 1998;Grant et al, 2001;Conroy et al;, Kollei et al, 2011. In dermatology settings, most studies have found BDD rates of 8.8-14% (Phillips et al, 2000;Uzun et al, 2003;Bowe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation